Percutaneous thermal segmentectomy using balloon-occluded microwave ablation fol lowed by balloon-occluded transarterial chemoembolization - Chlorogiannis, D-D; Spiliopoulos, S; Grigoriadis, S; Lucatelli, P; Filippiadis, D (Klinicka onkologie, 2025)
BACKGROUND: Solitary hepatocellular carcinoma (HCC) with a diameter of 3-5 cm represents a challenging clinical entity, especially for non-surgical candidates due to comorbidities. CASE: A 74-year-old man with previous history of renal cell carcinoma presented with a new incidental solitary 5 cm liver lesion on MRI. Due to his age and a high risk for post-surgical complications, after multidisciplinary tumor board review the treatment plan consisted of percutaneous thermal segmentectomy using balloon-occluded microwave ablation (b-MWA) followed by balloon-occluded transarterial chemoembolization (b-TACE) with complete tumor necrosis, as evident in subsequent follow-up imaging. This case demonstrates that b-MWA plus b-TACE could be a safe and effective combined therapy for unresectable large HCC lesions, even for those exceeding 3 cm in size. CONCLUSION: Although the presented case is anecdotal and naturally without comparisons or control, it highlights the potential value of percutaneous thermal segmentectomy with a single session combined b-MWA followed by b-TACE for the treatment of large unresectable solitary HCC lesions.
Keywords: Microwaves; balónková okluze; mikrovlny; hepatocelulární karcinom; hepatocellular carcinoma; Catheter Ablation; lidé; case report; nádory jater; Carcinoma, Hepatocellular; balloon occluded thermal ablation; katetrizační ablace; balloon occluded chemoembolization; chemoembolizace; Liver Neoplasms; Male; Aged; senioři; mužské pohlaví; Balloon Occlusion; Chemoembolization, Therapeutic; Humans